2005
DOI: 10.1038/sj.onc.1208591
|View full text |Cite
|
Sign up to set email alerts
|

The adaptor Grb7 is a novel calmodulin-binding protein: functional implications of the interaction of calmodulin with Grb7

Abstract: We demonstrate using Ca 2 þ -dependent calmodulin (CaM)-affinity chromatography and overlay with biotinylated CaM that the adaptor proteins growth factor receptor bound (Grb)7 and Grb7V (a naturally occurring variant lacking the Src homology 2 (SH2) domain) are CaM-binding proteins. Deletion of an amphiphilic basic amino-acid sequence (residues 243-256) predicted to form an a-helix located in the proximal region of its pleckstrin homology (PH) domain demonstrates the location of the CaM-binding domain. This si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 53 publications
2
57
0
Order By: Relevance
“…phoinositide-binding domain that is responsible for plasma membrane localization and is also accessible for phosphorylation by FAK (3,4). Structural prediction and biochemical validation both support the direct interaction of the RA domain with Ras-GTPases, similar to the canonical ubiquitin-like folded Ras-binding domain of c-Raf and RalGDS (5).…”
mentioning
confidence: 85%
“…phoinositide-binding domain that is responsible for plasma membrane localization and is also accessible for phosphorylation by FAK (3,4). Structural prediction and biochemical validation both support the direct interaction of the RA domain with Ras-GTPases, similar to the canonical ubiquitin-like folded Ras-binding domain of c-Raf and RalGDS (5).…”
mentioning
confidence: 85%
“…Moreover, GRB7 is implicated in cell invasion and metastatic progression of esophageal carcinoma (19,49). Recently, GRB7 has been shown to interact with calmodulin, which may contribute to the high motility observed in many cancer cells, their metastatic spread, and the neovascularization required for tumor progression (50). MLN64 is expressed preferentially in malignant tissues, specifically breast tumors and breast cancer cell lines, but not in normal cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between GRB7 and multiple cell surface receptors is known to mediate signal transduction to diverse downstream signaling pathways (Shen & Guan 2004). Several studies have demonstrated that GRB7 plays a key role in cell migration through its association with focal adhesion kinase, phosphoinositides, ephrin receptor EphB1, and calmodulin (Han et al 2000, 2002, Shen et al 2002, Li et al 2005, thus implying a likely role in tumor progression. For example, GRB7 expression has been associated with an invasive phenotype and metastatic progression of tumor cells in esophageal carcinoma (Tanaka et al 1997(Tanaka et al , 2000.…”
Section: Candidate Target Genes At the 17q12-q21 Ampliconmentioning
confidence: 99%